Pendampingan Pembelajaran Sastra Berbasis Tematik untuk Meningkatkan Kemampuan Literasi Numerasi Tingkat Sekolah Dasar - Fadila, Rizki; Ritonga, Mara Untung; Wuryani, Dr. Elly Prihasti (Cattleya Darmaya Fortuna, 2024)
Strengthening literacy, numeracy and character skills is an important effort to improve the quality of human resources in the Digital Age and the Era of Disruption. As a teacher or education personnel, developing students' activeness so that they can apply numeracy skills well is a big responsibility. The numeracy skills in question are number concepts and arithmetic operation skills used for daily life skills. This service activity aims to provide numeracy literacy-based learning process assistance to junior high school teachers in Medan City to improve the ability of teachers to create Numeracy Literacy HOTS questions. This activity is carried out in several stages, namely the team preparation stage, school observation, making modules/materials to be delivered to mentoring activities. In delivering the material, the community service team used various methods, questions and answers, discussions, lectures and assignments. All of these methods are used as needed. The result of the activity is that teachers can develop HOTS-based questions in groups according to their respective subjects. The group was chosen in order to provide a positive stimulus to teachers who do not know and understand the preparation of HOTS-based questions on Numeracy Literacy to be encouraged to be able to compile independently and apply in preparing evaluation questions to students.